The MINOM Rio 2013 Declaration - “Sustainable” and “Pro-vocative” treaty at the beginning of the 21st century (Cadernos de Sociomuseologia, 2015)
This paper discusses some aspects of the Declaration MINOM Rio 2013. The text shows the importance of this Declaration in the context of the early twenty-first century. The practical proposal of the document allows its use in other areas of knowledge and other segments of society. Therefore, the article presents two virtues of the Declaration: the questioning of established hierarchies and the presence of a hermeneutics of transdisciplinarity. Finally, the article concludes with the questions about the survival of these new movements of the community. Therefore proposes the methodology of Negócios Sócio-Sustentáveis WTS.  Keywords: Declaration MINOM Rio 2013, Hierarchies, Transdisciplinarity and Negócios Sócio-Sustentáveis WTS.